Foreign companies’ operative decisions in conflict zones – stay or exit? - Lindström, Roope (My University, 2025)
The purpose of this bachelor’s thesis is to examine how conflicts shape the business environment and the decision-making in international companies. This topic is important as globalization, the emergence of new and prominent markets, as well as the rise of small and medium-sized enterprises (SMEs) in the global perspective have made the global business environment (GBE) more interconnected than ever before – making international companies more volatile to shocks and changes. An unfortunate and growing trend concerning this is the augmentative number of conflicts around the world. International companies are therefore in need of crucial knowledge of the various nuances surrounding conflicts and conflict-affected decision-making. First, this thesis delves into the different types of conflict to illustrate their differences and discusses the various implications they pose for international companies. The thesis defines conflicts as non-violent or violent and places an emphasis on violent conflicts, as they pose the most risk for international companies. These conflicts regarding the degree of violence were divided into five different intensity levels, of which level five, wars, is the most severe. In addition, the different conflict types are discussed from the perspective of conflict partakers. These types are interstate, intrastate, substate, and trans-state. Moreover, as violent conflicts seem to occur more frequently in less-developed economies, possible reasons for that are examined through the scope of causal mechanisms. These mechanisms are greedy rebels, greedy outsiders, grievances, weak states, sparse networks, and feasibility. To get an idea of what it is like to essentially operate in a conflict-torn country, the economic consequences are discussed with the help of key economic and social indicators. These consist of changes in real economy, general government, and balance of payments. These aspects highlight the real-life scenery for international companies in conflict-torn countries. Consequently, the management of these companies have to consider these implications and decide, whether to stay or exit the country. As there are many factors that affect decision-making, some of the general ones are examined, which are categorized as firm-specific considerations, host country environment, and international arena. Moreover, the host country’s role in the conflict is discussed. To scan how international companies act in practice, the small-world representation constructed by conflict-afflicted managers is examined in terms of discover and evaluation heuristics. The thesis uncovers that reasons for conflict are not homogeneous. In less-developed countries, conflicts arise from many unrelated causes. While these vary by context, grievances, such as perceived injustice or inequality, gained a robust status, as well as weak states. It is also discovered that conflicts pose various implications for international companies. Alongside general conflict consequences, such as the drop in economic growth and exports and imports, the scale of external financial aid and migration were found to have a profound effect to a country’s economic welfare. Examining the decisive factors behind leaving or staying the conflict-torn country, the host-country’s role in the conflict was found to have ambiguous effects for companies. Received scrutiny in terms of reputational risks were found to be taken into consideration hand in hand with the usual operational risks, such as at-risk resources and investment compositions, especially in larger companies, as they face more spotlight from NGOs. Finally, a total of nine higher-order heuristics were discovered behind the small-world representations (SWRs) managers facing conflicts form. Information accessibility equipped with prior experience were found paramount in order to make high-class SWRs regarding the final decision about staying or exiting.

Tämän kandidaatintutkielman tarkoituksena on tarkastella, miten konfliktit muokkaavat liiketoimintaympäristöä ja päätöksentekoa kansainvälisissä yrityksissä. Aihe on ajankohtainen, sillä globalisaatio, uusien ja merkittävien markkinoiden nousu sekä pienten ja keskisuurten yritysten kasvava rooli globaalissa mittakaavassa ovat tehneet globaalista liiketoimintaympäristöstä entistä verkottuneemman, joka on samalla lisännyt kansainvälisten yritysten haavoittuvuutta erilaisille shokeille ja muutoksille. Valitettavasti yksi lisääntynyt ja huolestuttava ilmiö tässä kontekstissa on konfliktien määrän kasvu maailmanlaajuisesti. Kansainväliset yritykset tarvitsevatkin entistä syvempää ymmärrystä konfliktien erityispiirteistä ja niihin kytkeytyvästä päätöksenteosta. Tutkielman alussa tarkastellaan erilaisia konfliktityyppejä niiden välisten erojen havainnollistamiseksi ja analysoidaan, millaisia vaikutuksia niillä voi olla kansainvälisille yrityksille. Konfliktit jaetaan väkivallattomiin ja väkivaltaisiin, joista painotus keskittyy väkivaltaisiin konflikteihin, sillä ne muodostavat suurimman riskin kansainvälisille yrityksille. Väkivallan asteen mukaan konfliktit jaotellaan viiteen intensiteettitasoon, joista viides, sodat, on vakavin. Lisäksi konfliktityyppejä käsitellään osapuolten mukaan: valtioidenväliset, valtion sisäiset, valtionalaiset ja valtioiden rajat ylittävät konfliktit. Koska väkivaltaiset konfliktit näyttävät esiintyvän useammin kehittymättömissä talouksissa, pohditaan mahdollisia syitä ilmiölle ns. kausaalisten mekanismien avulla. Näitä ovat ahneet kapinalliset, ahneet ulkopuoliset, tyytymättömyys, heikot valtiot, harvat verkostot ja toteutettavuus. Jotta voidaan hahmottaa, millaista liiketoiminta konfliktialueella käytännössä on, konfliktien taloudellisia seurauksia tarkastellaan keskeisten taloudellisten ja yhteiskunnallisten indikaattorien avulla. Näihin kuuluvat reaalitalouden, julkisen talouden ja maksutaseen muutokset. Nämä tekijät kuvaavat konkreettisesti kansainvälisten yritysten toimintaympäristöä konfliktien keskellä. Tämän seurauksena yritysjohdon on arvioitava näiden vaikutusten merkitystä ja tehtävä päätös siitä, kannattaako maassa pysyä vai vetäytyä sieltä. Koska päätöksentekoon vaikuttaa useita tekijöitä, tutkielmassa tarkastellaan yleisiä vaikuttimia, jotka jaotellaan yrityskohtaisiin tekijöihin, isäntämaan ympäristöön sekä kansainväliseen toimintakenttään. Lisäksi isäntämaan roolia konfliktissa tarkastellaan sen mukaan. Jotta voidaan selvittää, miten kansainväliset yritykset toimivat käytännössä, analysoidaan konfliktista kärsivien johtajien muodostamia pienoismaailmakuvia tiedonhakuun ja arviointiin liittyvien heuristiikkojen näkökulmasta. Tutkielma paljastaa, että konfliktien syyt eivät ole yhtenäisiä. Vähemmän kehittyneissä maissa konfliktit syntyvät usein monista toisistaan irrallisista syistä. Vaikka taustat vaihtelevat kontekstin mukaan, esimerkiksi koettu epäoikeudenmukaisuus ja eriarvoisuus nousivat vahvasti esiin, samoin kuin heikot valtiot. Konfliktien todettiin aiheuttavan monenlaisia vaikutuksia kansainvälisille yrityksille. Yleisten seurausten, kuten talouskasvun hidastumisen sekä tuonnin ja viennin vähenemisen lisäksi ulkopuolisen taloudellisen avun ja muuttoliikkeen mittakaavan havaittiin vaikuttavan merkittävästi maan taloudelliseen hyvinvointiin. Päätöksenteon taustalla olevia tekijöitä, jäädäkö vai vetäytyä konfliktista kärsivästä maasta, tarkasteltaessa isäntämaan roolin havaittiin vaikuttavan yrityksiin moniselitteisesti. Mainehaittoihin liittyvä julkinen tarkastelu otettiin huomioon yhdessä tavanomaisten operatiivisten riskien kanssa, kuten uhattujen resurssien ja investointirakenteiden, erityisesti suuremmissa yrityksissä, jotka joutuvat enemmän kansalaisjärjestöjen huomion kohteeksi. Lopuksi havaittiin, että yhteensä yhdeksän korkeamman tason heuristiikkaa vaikuttavat johtajien muodostamiin pienoismaailmakuviin. Tiedon saatavuus yhdistettynä aiempaan kokemukseen osoittautui keskeiseksi, jotta johtajat pystyvät muodostamaan korkeatasoisia pienoismaailmakuvia lopullista päätöstä, jäämistä tai lähtöä, varten.
Keywords: international company, conflict, decision-making, small-world representation, kansainvälinen yritys, konflikti, päätöksenteko, pienoismaailmakuva